Como é triste essa página : as dinâmicas de interação e interferências subjetivas dos profissionais de publicidade que trabalham com novas mídias - Rosa, Letícia Gomes da (2016)
This thesis deals with the universe of Brazilian advertising professionals, focusing on the city of Porto Alegre. Search portray the organizational climate, scenery, dynamic interaction and subjective interference such as the advent of new media. Considered as reference the social networking site, Facebook. Part in research on the literature review about the changes in advertising from the rise of the internet and especially social networks. The method used in the section of our own was the case study with multiple units of analysis: Three advertising agencies that work with content management and monitoring of social networks. three techniques of data collection were applied: intensive direct observation in three advertising agencies, in-depth interviews with four advertising and documentation. From the description of the workplace, questioning respondents about the role of the advertising agency in the definition of communication strategies for their clients, training of professionals, the services offered, the customer relationship beyond the contemporary advertising market problems with the new media. The main result is that for the meaning of Facebook in professional practices, it is changes in the staff of agencies, ranging from the integration of a new professional, social media. To an adaptation of the functions already present in order to better serve customers that require the management of social networking sites. Change in customer service, relationship between client and agency, requiring this greater presence with your customer. Finally, a change in the understanding of practices focusing on the development of ads.